The Role of Forensic Accounting in Detecting Financial Fraud - الجبوري, نصيف جاسم; محمد, صلاح هادي (Journal of Economics and Administrative Sciences, 2013)
A Forensic Accounting is represent science that deals with the application of knowledge in the areas of accounting, finance, tax and audit for the analysis, investigation, inquiry, inspection and testing issues in the civil law and criminal law in an attempt to reach the truth through which enable the Forensic Accountant to provide his Expert opinion , forensic accounting plays a major role by providing a range of important services in the field of investigation for fraud and litigation support, As one of the most important legal and accounting functions is to investigate allegations of alleged by the related parties, especially those allegations related to the existence of fraud, since the goal of judicial accountant will depend on the purpose of the assignment may be the task of investigating the existence of fraud or quantization some economic damage. Fraud has spread dramatically in many companies due to depending of chartered accountant on the sample method when auditing the financial statements and Absence of his liability to detecting fraud , and here comes the importance of forensic accounting in the detection of fraud by employing a range of techniques which help in the detection of fraud. As that investigation forensic accountant objectives requires that they enjoy a range of characteristics, such as education, training and varied experience in the field of accounting, auditing and law, and communication skills - oral and written, the ability to work in a team environment. And dependent judicial accountability in their work on a variety of techniques including benford law, and audit the use of CAATs and data mining and analysis ratios.